PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. ASTRA HONDA NUSA DUA KABUPATEN BADUNG - Setiawan, Kadek Ary; Mujiati, Ni Wayan (E-Jurnal Manajemen, 2017)
The purpose of this study was to determine the effect of leadership style and compensation to employee performance. This research was conducted at PT. Astra Honda Nusadua Badung regency of Bali. The population of as many as 35 people. The sampling method used is sampling saturated, so that all the population is used as a sample. Data collected through interviews and observations. The analysis tool used is multiple linear regression techniques. Results of the analysis showed that the style of leadership and significant positive effect on employee performance. This shows that if the leadership style increases the employee's performance will increase significantly. Variable compensation positive and significant effect on employee performance. This shows that if the provision of fair and adequate compensation given to employees, the employees performance will increase significantly.
Keywords: leadership style; compensation; employee performance